KELEKATAN ANAK DENGAN IBU DAN AYAH SERTA PERILAKU PORNOGRAFI PADA ANAK USIA SMP - Hardani, Rika; Hastuti, Dwi; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2017)
The mother’s attachment and father’s attachment with children were formed since childhood, will influence the future development of the child's personality. A good personality will make children able to choose good behavior and not to fall into negative behaviors such as behavioral pornography. The research aimed is to analyze the influence of mother-child's attachment and father-child’s attachment on the behavior of school-age child pornography (SMP). The choice of location was purposively in South Tangerang City. A total of 600 children aged junior consisting of 278 men and 322 women were selected using cluster random sampling technique with the class as a cluster of selected schools in the study sites. Respondents were asked to fill out questionnaires of the Inventory of Parent and Peer Attachment (IPPA) and the questionnaire Pornography Behavior. Data were analyzed with descriptive analysis, correlation, and regression. The results showed that the boys and girls of mother’s attachment score higher than father’s attachment scores. Behavior pornography on boys is higher than girls. The mother’s attachment and father’s attachment showed a significant negative correlation with the behavior of pornography. Regression analysis showed that family income significant positive effect on the behavior of pornography. Instead, the mother’s attachment and father’s attachment significant negative effect on the behavior of pornography.